(untitled) (Journal of the College of Basic Education, 2023)
The current research aimed at the effect of the generative learning strategy on the cognitive achievement of the third stage students of the Department of Physical Education and Sports Sciences, College of Basic Education, Al-Mustansiriya University, with the subject of teaching methods. If the research community consists of four halls (1, 2, 3, 4) and their number is (118) students, and the sample was chosen by random method (lottery), which was represented by halls (1 and 3), the experimental group numbering (62) and halls (2 and 4). The control group, which numbered (56) students, thus the number of the sample became (118), then (18) students (12) were excluded from the experimental group and (6) Of the remaining control group, they are those who are late, absent and non-compliant. Thus, the actual number of the experiment was (100). The researcher adopted the cognitive achievement test, where he conducted a pre-test for the two groups, a post-test for the two groups, and a test for another exploratory group. After completing the experiment, the results were statistically analyzed using the post test for the two groups, and the results showed that the experimental group using the generative learning strategy was superior to the control group, and the researcher concluded the following: The generative learning strategy proved to be effective in increasing students’ cognitive achievement, and the generative learning strategy proved to bring comfort to the students and increased the research sample.